A content analysis of literature on islamic space planning as related to its religious principles - Nepomuceno, Angela Viola; Florendo, Raquel Baltazar (2008.)
The main focus of the study is to identify the discussion of space planning in relation to Muslim religious principles in literature. As a content analysis study, the inquiry recognizes that written sources can be used as sources of data that may be coded and reinterpreted to provide explanations on certain phenomena. The gathered data may be used to provide baseline research on space planning concepts related to spiritual principles of Muslim; which may be useful in the field of design and cultural studies needed both by academicians and design practitioners. The data gathering instrument used is content analysis matrix encoding the key thematic categories on Muslim spiritual practices, beliefs and principles, derived from a purposive sample of eight books in Muslim space use. Using a content analysis tabulation, the data was tallied to arrive at a frequency distribution. The researcher computed for the percentage of occurrence of each Islamic principle drawn from the literature sources. The results were then presented using a pie chart to indicate the respective percentage of each category. Analysis of data using a content analysis format derives explanation and interpretation of data drawn from the thematic substance of the written document and literature on the topic. Results of the study identified the following unique characteristics of Islamic space planning: 1) the presence of a one-room dwelling, 2) its impermanent and multi-functional character, 3) the segregation of transitional and private spaces for women, and 4) the provision for a place of worship and the Holy Text, the Qu'ran. A courtyard or a garden, and the orientation to Mecca, are often also a physical component. On the other hand, the significant religious principles that explain and relate to these characteristics include: 1) the concept of Tahwid, 2) the Islamic cosmology, 3) the concept of man as 'Khalifa', 4) the segregation of women, 5) domestic privacy and 6) the concept of a 'religious home'. Among these concepts, the most frequently used in all written sources and therefore the most important and significant religious principle is the concept of Tahwid. The concept of Tawhid highlights open or void spaces to make communication or 'union' with the Divine possible. For Muslims, an open space signifies the presence of Allah. Thus, Muslim spirituality is embedded in the physical aspect of their spaces. In the future design projects catering to Muslim families or individuals, it is recommended to take into consideration the norms set by the religion. Because of the huge influence of the Islamic religion to the lives of the Muslims, it is important to know how these religious principles can be utilized in interior space, not only to address the standards of the Islamic religion but also to help preserve the valuable Muslim tradition.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Architecture, Islamic -- Philippines; Interior decoration -- Islamic influences